L’héritage de l’immigration postcoloniale comme expérience vécue - Ahmed Boubeker (Amnis, 2007)
The emergence of “immigration” in French public space raises the essential issue of the misunderstandings between history and memory, and underlines the need for a critical revision of the great national narrative. The link between collective memory and national memory is questioned by other narratives confined until recently as clandestine memoirs, but which now find place on the media and cultural scene. When a National City of the History of Immigration opens its doors, this article questions the inheritance of immigration as a lived experience. It tries to put in perspectives the conditions for the recognition of a political memory of the fights of forgotten ones in history, supporting a questioning of the old hierarchies in the writing of history. But it also underlines the possible faults of a patrimonialisation of immigration which, far from an actual recognition, could participate in a public instrumentalisation of memory.